Penegakan Hukum Pidana Terhadap Praktik Penggelapan Pajak Oleh Badan Usaha (Studi Pada Kantor Pelayanan Pajak Pratama Kuala Tungkal) - Hisbah Hisbah; Nur Anisah (Legalitas: Jurnal Hukum, 2026)
Tax is a mandatory contribution to the state that is mandatory and must be paid by every taxpayer in accordance with the provisions of the laws and regulations. Tax evasion is an attempt made by taxpayers, in this case business entities, to reduce or avoid their tax obligations by means that violate the law. The purpose of this study is to analyze the implementation of criminal law enforcement against tax evasion by business entities at the Kuala Tungkal Pratama Tax Service Office, identify the obstacles faced by the tax authorities in the disclosure process, and examine the efforts made by the tax authorities in uncovering and overcoming tax evasion practices by business entities. The method used in this study is an empirical juridical research method. Data collection in this study was conducted through interviews. From the results of this study, it can be concluded that criminal law enforcement against tax evasion by business entities at the Kuala Tungkal Pratama Tax Service Office is running systematically from supervision to investigation, although hampered by limited technical human resources, asset tracking, and inter-agency coordination. The tax authorities face complex, interrelated challenges, thus weakening the recovery of state losses. Preventive efforts through socialization and synergy, as well as repressive efforts via inspections, build formal-material compliance in a sustainable manner